2016
DOI: 10.1039/c5nr08697c
|View full text |Cite
|
Sign up to set email alerts
|

A reduced graphene oxide nanofiltration membrane intercalated by well-dispersed carbon nanotubes for drinking water purification

Abstract: In this study, we report a promising rGO-CNT hybrid nanofiltration (NF) membrane that was fabricated by loading reduced graphene oxide that was intercalated with carbon nanotubes (rGO-CNTs) onto an anodic aluminum oxide (AAO) microfiltration membrane via a facile vacuum-assisted filtration process. To create this NF membrane, the CNTs were first dispersed using block copolymers (BCPs); the effects of the types and contents of BCPs used on the dispersion of CNTs have been investigated. The as-prepared rGO-CNT h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(94 citation statements)
references
References 52 publications
1
93
0
Order By: Relevance
“…Recently, Chen et al reported a novel CNTs-based composite membrane that was fabricated by loading reduced graphene oxide and CNTs onto an AAO membrane via vacuum filtering (as shown in Figure 9). The as-prepared composite membranes showed high permeability and separation performance for drinking water purification [87]. …”
Section: Fabrication Methods Of Cnts-based Composite Membranesmentioning
confidence: 99%
“…Recently, Chen et al reported a novel CNTs-based composite membrane that was fabricated by loading reduced graphene oxide and CNTs onto an AAO membrane via vacuum filtering (as shown in Figure 9). The as-prepared composite membranes showed high permeability and separation performance for drinking water purification [87]. …”
Section: Fabrication Methods Of Cnts-based Composite Membranesmentioning
confidence: 99%
“…The resulting rGO/MWNTs were then loaded onto an anodic aluminum oxide microfiltration membrane via a vacuum-assisted filtration process [95]. This resulted in the preparation of a hybrid rGO/MWNT membrane that was then used to purify drinking water by retaining Au NPs and a wide range of organic compounds, including dyes, proteins, organophosphates, sugars, and humic acid.…”
Section: Filtration Applicationsmentioning
confidence: 99%
“…The antifouling nature of the membranes to HA and sodium alginate was good but protein fouling was not ideal. Improvements in flux due to enhancement in steric effects were realized by better dispersion and mixing of the CNT/GO layer by addition of pluronic surfactants (block copolymers) which were vacuum filtration deposited onto anodic Al 2 O 3 MF membranes [44]. Again, drying related shrinkage of films of this type have been reported and damage to films is possible under crossflow and high TMP conditions, although efforts to stabilise the film showed reasonable success by incorporation of a sacrificial layer of PMMA with in-situ reduction of GO using UV [45].…”
Section: Carbon Nanosheet Membranes For Desalinationmentioning
confidence: 99%